Numerical Simulation of Fracture Propagation Characteristics of Hydraulic Fracturing in Multiple Coal Seams, Eastern Yunnan, China - Wang, Kaifeng; Tang, Shuheng; Zhang, Songhang; Guo, Yingying; Lin, Donglin; Niu, Zhichao (Frontiers in Earth Science, 2022)
As a reservoir reconstruction technology, hydraulic fracturing is a key method to improve the production of coalbed methane (CBM) wells. The CBM reservoir in eastern Yunnan, an important CBM exploration and development zone in China, is characterized by multiple thin coal seams. Compared to the fracturing of single-layer coal seam, the combined seam fracturing technology is more difficult and complex. To study the fracture propagation characteristics and influencing factors of hydraulic fracturing in multiple coal seams, taking No. 9 and No. 13 coal seams as the research objects, the fracturing process was numerically simulated by finite element method and ANSYS software in this work. Based on the mathematical model of low permeable coal-rock mass, a two-dimensional hydraulic fracture model was established. In addition, the fracture geometries of combined seam fracturing were studied quantitatively. The results indicate that although No. 9 coal and No. 13 coal have similar rock mechanical properties, the propagation process and final geometry of fracture are different. The reliability of the simulation results is verified by the comparison of experimental parameters and field investigation. The results prove the feasibility of combined seam fracturing in eastern Yunnan. The high Young's modulus and thickness of coal seam make the fracture geometry longer, but the fracture height is smaller. The low Young's modulus, high Poisson's ratio and thickness of No. 13 coal seam result in increased the length and height of No. 9 coal seam. The increase of the Young's modulus of interlayer inhibits the propagation of fractures, while the high thickness and low Poisson's ratio of interlayer facilitate the extension of the length and inhibit the extension of the height. This work provides a case reference for combined seam fracturing of coal reservoir and has a practical significance for the development of CBM characterized by multiple coal seams in eastern Yunnan.